High-current electron beam guiding by the creation of profiled plasma channel - Agafonov, A.V.; Bogachenkov, V.A. (Вопросы атомной науки и техники, 2004)
Earlier performed experiments showed effectiveness of proposed approach for a high-current non-relativistic electron beam generation in a plasma-filled diode with a plasma anode and an explosive emission cathode. Our approach is
based on the application of an additional low-current electron beam. This beam is used for the plasma anode and the transportation channel generation with predictable parameters of plasmas by the residual or prefilled gas ionization.. Measurements of plasma channel parameters in a wide region of experimental conditions confirm that this approach possesses to
create radial profiled plasmas channels of desired plasmas density distribution for generation and transport of high-current
beams. Проведені раніше експерименти по генерації плазмових каналів з контрольованим профілем густини по
радіусі для генерації низькоенергетичного потужнострумового електронного пучка в плазмозаповненному
діоді з протяжним плазмовим анодом показали ефективність запропонованого підходу. У даній системі для
генерації плазмового анода і каналу транспортування з заданими параметрами в результаті іонізації
залишкового або спеціально напущеного в систему газу використаний допоміжний слабкострумовий пучок
електронів. Вимірювання параметрів плазмового каналу в широкому діапазоні експериментальних умов
показують, що такий метод дозволяє створювати радіально обмежені канали з необхідної густиною для
одержання потужнострумових пучків з різним розподілом густини по перерізу пучка. Проведенные ранее эксперименты по генерации плазменных каналов с контролируемым профилем
плотности по радиусу для генерации низкоэнергетичного сильноточного электронного пучка в плазмонаполненном диоде с протяженным плазменным анодом показали эффективность предложенного подхода. В
данной системе для генерации плазменного анода и канала транспортировки с заданными параметрами в результате ионизации остаточного или специально напущенного в систему газа использован вспомогательный
слаботочный пучок электронов. Измерения параметров плазменного канала в широком диапазоне экспериментальных условий показывают, что такой метод позволяет создавать радиально ограниченные каналы с
необходимой для получения сильноточных пучков плотностью с различным распределением ее по сечению.